Modelling of Simple Cross Docking Facility - Haridas, Anuroop (2013)
In the modern world, with resources running scarce and competition getting cut throat, efficiency and smarter operations are one among the inevitable objectives of any organisation. Cost reduction, time savings and better resource management are among the main concerns while running any profit motive organisation. Logistics and supply chain plays a major role in the sustainable running of businesses in the current world due to the dependence of suppliers from different regions and a wide spread customer base. Cross docking is one of the most efficient methods of consolidating and shipping goods from a variety of suppliers to different retail destinations. Cross dock is basically an intermediate hub between the suppliers and retailers. The goods arrive at cross dock from various suppliers in Full Truck Loads and they are sorted and consolidated into Full Truck Loads which can be sent to their final destination, which are usually smaller retail outlets. Even though cross docking is one of the efficient methods in distribution of goods, certain operational strategies can be implemented in a cross dock to further improve its efficiency. One such strategy would be to formulate an efficient method to sequence the tasks of transhipping the goods from inbound docks to the outbound docks. This dissertation aims at formulating an algorithm to find an efficient sequence of transhipping the containers within a cross dock, from inbound docks to the outbound docks. The facility considered is a single-stage cross dock with a linear orientation, i.e. all the docks are oriented along a straight line. The transhipment tasks are carried out by a single forklift traversing within the facility in a linear manner. The algorithms have been developed for two cases, one without precedence constraints for the tasks to be carried out and the other one considering the precedence constraints. Five algorithms have been proposed of which three are heuristic approaches. For the situation without precedence constraints, algorithms based on Arc Routing Method and Savings Heuristic is proposed. For the situation with precedence constraints the algorithms proposed are based on savings heuristic and enumeration. Another approach based on Project Management techniques is also developed, but needs further research and modification to be done to be implemented effectively in a cross dock. The performance of the methods is compared by analysing the results obtained on